Asymmetric Effects of Macroeconomic Variables on Stock Market Indices: Evidence From Developed and Emerging Economies - Imatul Hamza; Linda Karlina Sari; Sendy Watazawwadu’Ilmi Watazawwadu’Ilmi; Fuad Wahdan Muhibuddin (School of Business, IPB University, 2026)
Background: Global financial markets are increasingly integrated, yet the response of stock indices to macroeconomic shocks remains poorly understood in its nonlinear dimensions. Most existing studies adopt symmetric linear frameworks that may fail to capture the differential market reactions to positive and negative macroeconomic changes.Purpose: This study investigates the asymmetric effects of key macroeconomic variables, namely exchange rates, gross domestic product (GDP), and interest rates, on stock market indices across 56 countries classified into 28 developed and 28 emerging economies over the period 2016Q1 to 2024Q3.Design/Methodology/Approach: This study employs panel Autoregressive Distributed Lag (ARDL) and panel Nonlinear Autoregressive Distributed Lag (NARDL) models estimated through Pooled Mean Group (PMG), Mean Group (MG), and Dynamic Fixed Effect (DFE) estimators. The Hausman test is applied to determine the optimal estimator. Asymmetry is formally tested using the Wald test. Unit root analysis uses the Augmented Dickey Fuller (ADF) test, and cointegration is verified via the Kao panel cointegration test.Findings/Result: The NARDL model consistently outperforms the symmetric ARDL specification across all country groups based on Akaike Information Criterion (AIC). Significant long-run asymmetric effects are identified for all three macroeconomic variables. Currency depreciation exerts a larger negative impact on stock indices than appreciation across both country groups. GDP growth positively drives stock markets in developed economies but has no significant effect in emerging markets. Interest rate cuts generate larger stock market responses than equivalent rate increases. In the short run, GDP and interest rate movements display asymmetric effects in emerging economies, while developed markets are more resilient to short-term macroeconomic fluctuations.Conclusion: Asymmetric quantitative modeling significantly enriches the understanding of macroeconomic transmission mechanisms in financial markets, with critical implications for monetary policy design and investment risk management in both developed and emerging economies.Originality/Value: This study provides one of the first comprehensive panel NARDL analyses spanning 56 countries across both developed and emerging markets simultaneously over a post-2016 dataset, explicitly testing directional asymmetry in the GDP, exchange rate, and interest rate transmission to stock markets. The findings advance the limited literature that treats these relationships as symmetric. Keywords:asymmetric effects, macroeconomic variables, panel ARDL, panel NARDL, stock market index